China's three decades of economic reforms / edited by Xiaohui Liu and - Liu, Xiaohui. (ed.) (London, 2010)
In the thirty years since China initiated economic reforms and its open-door policy, China has been transformed from a poor nation almost completely isolated from the global economy to an engine of growth of the world economy. China$1 (Bs dynamic transition has been among the most dramatic developments of recent history; and its economy continues to grow rapidly, with important consequences for China$1 (Bs own society and environment, as well as for the wider world. This book provides a fascinating insight into a wide range of issues on Chinese economy and its three decades of economic reforms. With well-researched, in-depth and comprehensive coverage of key topics, using the latest research findings, this book covers Chinese monetary policy and financial sector reforms; China$1 (Bs income disparities; the emergence of China$1 (Bs business groups; the implications of foreign direct investment and innovation and technological developments. The book will be an indispensable guide to scholars, entrepreneurs, policy-makers and all who are interested in China$1 (Bs economic affairs.s
Keywords: China-Economic conditions 1976-2000